Production, characterization and scaling up of monoclonal antibodies against neuraminidase glycoprotein of avian influenza virus subtype H9N2 - Abdelaziz Fadul, Sana Awad (2011)
Avian influenza viruses (AIVs) are a group of pathogens responsible for many respiratory illnesses, infected human and animals worldwide. Although early detection of influenza diseases relied on conventional techniques, monoclonal antibodies (mAbs) have been reported to be useful in rapid detection, identification and treatment of influenza infections. In this study, monoclonal antibodies against neuraminidase (NA) protein of avian influenza virus A/Chicken/Iran/16/2000/H9N2 were produced to contribute to the enhancement of detection, diagnosis and control of avian influenza virus infections. Avian influenza virus (AIV) subtype H9N2 was propagated in embryonated chicken eggs. Propagated virus was purified and used as immunizing agent for Balb/c mice. Hybridoma clones were produced by fusing spleen cells from AIV-immunized mouse with SP2/O (myeloma cells) using polyethylene glycol (PEG) as fusing agent. Supernatant of constructed hybridomas was screened by ELISA for the detection of the antibodies. The highly positive clones were subjected to a series of limiting dilutions in order to ensure their monoclonality. Subclasses of the selected mAbs were determined; as well immunoblotting was performed to identify the specificity of produced mAbs. Clones which exhibited specificity towards NA protein were selected and characterized by neuraminidase inhibition test, elution inhibition test, and virus yield reduction in embryonated chicken eggs allantoic fluids. Characterization was extended by assessing the effect of anti-neuraminidase mAbs in neutralizing the virus in MDCK cells. Most importantly, cross reactivity was done to determine whether the produced mAbs exhibit cross-reaction to H5N1, H1N1, H3N2 and H3N8 influenza strains. The in vivo protection efficacy of anti-neuraminidase mAbs was evaluated in Balb/c mice, which were challenged with lethal dose of H9N2 viruses 24h before or after treatment with the antibodies. In order to study the large productivity of hybridoma culture, cells were grown in fed batch culture mode using cost effective spinner flask system. Seven hybrid cell lines that produced mAbs against H9N2 were developed and designated as 2H5, 4H2, 2A5, 2A12, 3C7, 5F3, and 3D7. Isotyping showed that 2H5 was IgG1; 3C7 was IgG2b; 4H2, 2A5, 2A12 and 5F3 were IgM and 3D7 was IgA. Kappa (κ) light chains were found in all mAbs. Immunoblot analysis of the clones revealed on only five clones’ that recognized H9N2 proteins. Among the five clones, mAbs 2H5 and 4H2 recognized NA protein, mAb 2A12 recognized HA protein and both 2A5 and 3C7 recognized M protein, whereas mAbs 5F3 and 3D7 did not match any epitope. The clones that produced mAbs against neuraminidase (NA) protein showed inhibitory effect on NA enzyme activity, strongly inhibited elution of the virus from RBCs, and reduced the virus yield in the infected allantoic fluids of embryonated chicken eggs. Furthermore, mAbs against NA inhibited virus replication in MDCK cells which led to viability percentages of 78.8 % and 75.2 % at 1000 μg/mL mAbs concentration for 2H5 and 4H2 clones, respectively. The reactivity of each mAb with several subtypes of influenza virus revealed that clones 2H5 and 4H2 react strongly with H5N1, H1N1 and H3N2 strains. All clones showed moderate to weak reactivity towards H3N8. It was observed that pre treatment with anti-neuraminidase mAbs protect mice totally (100 %) from the virus induced mortality, with remarkable reduction in severity of the clinical symptoms and reduction of lung virus shedding to 22.8 and 23 HAUs at dose 10 mg/kg of body weight for 2H5 and 4H2, respectively. Whereas, protection values of the mAbs administered 24 h post infection, did not show complete protection even when they were administrated at high doses (62.5% protection). In fed batch culture with the continuous addition of nutrients, antibodies reached concentrations of 550 mg/L and maximum cell density and viability of about 6.8 × 106 cells/mL and 96.9%, respectively. Compared with the results obtained from the conventional batch culture, the antibodies concentration was about 320 mg/L, and cell density and viability were lasted at around 1.2 x106 cells/mL and 51.3%, respectively. The addition of nutrient medium in fed batch process, maintained the continuous supply of nutrients specially glucose and glutamine and kept their by-products lactate and ammonia at low levels, which led to the enhancement of productivity in terms of antibodies concentration, cell density and cell viabilities. In conclusion, this study had constructed and characterized monoclonal antibodies against NA protein of H9N2 virus which act effectively in inhibiting neuraminidase enzyme in vitro and in vivo. These monoclonal antibodies may have the potential to be used for detection, diagnosis and therapy of avian influenza virus infections.